Phenolic compounds from the seeds of Scaphium macropodum (MIQ.) Beumée - Thanh, Nguyen Van; Toan Phan, Nguyen Huu; Duc, Hoang Thi; Thu Hien, Nguyen Thi; Dieu Thuan, Nguyen Thi; Tu, Vu Anh; Cuong, Nguyen Xuan; Nam, Nguyen Hoai; Minh, Chau Van (Vietnam Journal of Chemistry, 2015)
Five known compounds 6,7,9α-trihydroxy-3,8,11α-trimethylcyclohexo-[d,e]-coumarin (1), mansonone H (2), (R)-lasiodiplodin (3), trans-p-coumaric acid (4) and 3,4-dihydroxybenzaldehyde (5) were obtained from the organic extract of the seeds of Scaphium macropodum (Miq.) Beumée by various chromatographic techniques. Structural elucidation of the metabolites was carried out by analysis of their spectroscopic data and by comparison with those reported in the literature. All the compounds were isolated from this plant for the first time. Keywords. Scaphium macropodum, Sterculiaceae, phenolic compound.